Examining the Effect of Textual Enhancement on the Students’ Grammar Achievement - Julien Arief Wicaksono; Nodistya Septian Indrastana; Gullit Tornado Taufan; Renata Kenanga Rinda (Journey: Journal of English Language and Pedagogy, 2023)
This recent research was conducted to examine the effectiveness of textual enhancement on the students’ grammar achievement, in this case passive voice. Two kinds of instruction were implemented to two groups. The first instruction was enhanced instruction which consisted of textual enhancement and rule explanation, and the other instruction was explicit only instruction which consisted of rule explanation only. The study used quasi-experimental research design. A test was used in the pre-test and post-test to get the students’ score as the main data to be compared. From the result of the test analysis, finding shows that textual enhancement contributed a significant effect on the students’ passive voice achievement. Moreover, from the result of the questionnaire as the supporting instrument, the textual enhancement was more effective to be implemented to those which were considered as the low achievers than those considered as the high achievers. The students were more aware, focus, and easier in recognizing the pattern of passive voice